Weak Measurement of Elliptical Dipole Moments by C -Point Splitting - Nechayev, Sergey; Neugebauer, Martin; Vorndran, Martin; Leuchs, Gerd; Banzer, Peter (Physical Review Letters, 2018)
We investigate points of circular polarization in the far field of elliptically polarized dipoles and establish a relation between the angular position and helicity of these C points and the dipole moment. In the case of highly eccentric dipoles, the C points of opposite handedness exhibit only a small angular separation and occur in the low intensity region of the emission pattern. In this regard, we introduce an optical weak measurement approach that utilizes the transverse electric (azimuthal) and transverse magnetic (radial) far-field polarization basis. Projecting the far field onto a spatially varying postselected polarization state reveals the angular separation and the helicity of the C points. We demonstrate the applicability of this approach and determine the elliptical dipole moment of a particle sitting on an interface by measuring the C points in its far field.
CRIS-Team Scopus Importer:2023-04-20